Determination of critical control points in the process of freezing whole gutted scale red snapper at PT Alam Jaya Surabaya - Aliyah, Salsabila Diva; Kumala, Yufinca Mellyafara Indra (Journal of Marine Resources and Coastal Management, 2023)
Red snapper is a type of food that is easily damaged and rotten. To maintain the freshness of fish for a long period of time, preservation can be done, one of which is by storing the fish at a low temperature or called freezing. During the freezing process biological, physical and chemical changes occur. Control measures are needed to prevent and minimize damage to red snapper products by implementing Critical Control Points (CCP), namely a step where controls can be carried out to prevent or eliminate food safety hazards. The aim of this research is to determine the application of CCP in freezing red snapper at PT Alam Jaya Surabaya through interviews with the Quality Control section and employees of PT Alam Jaya Surabaya as well as direct observation within the scope of CCP. PT Alam Jaya Surabaya has two CCPs, i.e. raw materials receiving (sorting) and the metal objects checking using metal detector. Corrective action taken in the process of receiving raw materials is by carrying out laboratory tests and organoleptic tests, as a form of prevention, as well as rejecting raw materials that do not meet standards. In the metal objects checking process, the corrective action that must be taken is to carry out calibration if deviated results are found, repair by a technician if an error occurs in the detector machine, as well as rejecting and not sending the product if the product contains metal fragments.